Numerical Study of Air Cushion Effect in Notched Disk Water Entry Process Using Structured Arbitrary Lagrangian–Eulerian Method - Zhe Zhang; Nana Yang; Jinlong Ju; Xingzhi Bai; Houcun Zhou; Wenhua Wu (Journal of Marine Science and Engineering)
This paper presents a novel numerical investigation into the air cushion effect and impact loads during the water entry of notched discs, utilizing the Structured Arbitrary Lagrangian–Eulerian (S-ALE) algorithm in LS-DYNA. Unlike prior studies that focused on smooth or unnotched geometries, the present study explores how varying notch parameters influence the fluid–solid coupling process during high-speed water entry. The reliability and accuracy of the computational method are validated through grid independence verification and comparisons with experimental data and empirical formulas. Systematic analysis of the effects of notch size, water entry velocity, and entry angle on the evolution of the free surface, impact loads, and structural responses uncovers several novel findings. Notably, increasing the notch diameter significantly enhances the formation and stability of the air cushion, leading to a considerable reduction in peak impact loads—a phenomenon not previously quantified. Additionally, higher water entry Froude numbers are shown to accelerate air cushion compression and formation, markedly affecting free surface morphology and force distribution. The results also reveal that varying the water entry angle alters the air cushion’s morphological characteristics, where larger angles induce a more pronounced but less stable air cushion, influencing the internal structural response differently across regions.